2004
DOI: 10.1021/ac040004c
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Surface Plasmon-Coupled Emission Using Thin Aluminum Films

Abstract: Surface plasmon-coupled emission (SPCE) is the directional radiation of light into a substrate due to excited fluorophores above a thin metal film. To date, SPCE has only been observed with visible wavelengths using silver or gold films. We now show that SPCE can be observed in the ultraviolet region of the spectrum using thin (20 nm) aluminum films. We observed directional emission in a quartz substrate from the DNA base analogue 2-aminopurine (2-AP). The SPCE radiation occurs within a narrow angle at 59° fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
97
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 28 publications
0
97
1
Order By: Relevance
“…It is however worth noting that the signal at the SPCC peak angle is not entirely ppolarized. This is in contrast with our past experiences with optically pumped SPCE experiments where the SPCE signal was almost entirely p-polarized [8][9][15][16][17][18][19][20]. Figure 2 (Bottom) is the normalized SPCC and free-space emission spectra showing a high degree of overlap between the spectra.…”
Section: Resultscontrasting
confidence: 66%
See 3 more Smart Citations
“…It is however worth noting that the signal at the SPCC peak angle is not entirely ppolarized. This is in contrast with our past experiences with optically pumped SPCE experiments where the SPCE signal was almost entirely p-polarized [8][9][15][16][17][18][19][20]. Figure 2 (Bottom) is the normalized SPCC and free-space emission spectra showing a high degree of overlap between the spectra.…”
Section: Resultscontrasting
confidence: 66%
“…This is unlike our previous experiences with optically pumped SPCE studies for a thin layer of fluorophores, where the SPCE peak angle was approximately 1-2 degrees [8][9][15][16][17][18][19][20]. In order to investigate if the broadness of the SPCC peak is dependent on the surface area of the sample, we repeated the experiment with a sample chamber built inhouse that had approximately half the surface area when compared to the samples made with commercially available imaging chambers that had been used thus far.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…18 However, it has been shown that excited fluorophores over smooth aluminum film could create surface plasmons, which eventually radiate into the substrate. 19 The spectral properties of the radiation were found to be essentially identical to those of the fluorophore, except for a highly p-polarized emission. The angular dependence of the radiation, as well as the p-polarization, are consistent with radiating surface plasmon.…”
mentioning
confidence: 86%